2016
DOI: 10.1088/1674-1056/25/11/114702
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional detonation cellular structures in rectangular ducts using an improved CESE scheme

Abstract: The three-dimensional premixed H 2 -O 2 detonation propagation in rectangular ducts is simulated using an in-house parallel detonation code based on the second-order space-time conservation element and solution element (CE/SE) scheme. The simulation reproduces three typical cellular structures by setting appropriate cross-sectional size and initial perturbation in square tubes. As the cross-sectional size decreases, critical cellular structures transforming the rectangular or diagonal mode into the spinning mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Shen et al [32] found that with the duct width decreasing, the rectangular out-ofphase can be obtained with a rectangular initial perturbation. Therefore, we decrease the grid size to N x × N y × N z = 600 × 160 × 160 to find out whether the rectangular out-of-phase can be observed.…”
Section: Unsteady Detonationmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al [32] found that with the duct width decreasing, the rectangular out-ofphase can be obtained with a rectangular initial perturbation. Therefore, we decrease the grid size to N x × N y × N z = 600 × 160 × 160 to find out whether the rectangular out-of-phase can be observed.…”
Section: Unsteady Detonationmentioning
confidence: 99%
“…Dou et al [26], Wang et al [27] and Borisov et al [28] adopted the fifth-order weighted essentially non-oscillatory method to conduct a high resolution simulation of 3D detonations and study the influence of different factors (e.g., tube width, specific heat ratio and initial perturbation) on the structure of detonation waves. In addition, different mathematic models have been developed to solve the reactive Euler equations for the purpose of reducing the memory usage and computational time [29,30,31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The radius of fuel droplets is 50 µm. [20] In order to simulate the initial ignition spark, 15 ambient pressures and 15 ambient temperatures are specified in the range of x/l ≤ 0.01 and r/r 0 ≤ 0.5, [21,22] where l is the length of the tube and r 0 is the radius of the tube. The external flow field is filled with air at the normal temperature and pressure.…”
Section: Formulation Of Physical and Numerical Modelsmentioning
confidence: 99%